Synthesis and Biological Effectiveness of Some new Azo Compounds as Derivatives of Nitrogen Bases - Baghdad Science Journal (مجلة بغداد للعلوم, 2016)
In this study the new azo compounds (3compounds) for nitrogen bases (Adenine and Cytosine) are synthesized through two reaction steps (formation of diazonium salt and coupling reaction). The compounds have been characterized by FTIR, melting point, and ultra-violate (UV) spectra. All synthesized compounds have been estimated in vitro for their antimicrobial activities against two species of bacteria(E.coli, S.aureus)and one kind of fungi ( Aspergillus flavus) .The results show that these compounds have very good antibacterial and antifungal activities especially compounds 1 and 3.To study the effect of these compounds were making some physiological tests on rats are made ,the results of hematological study showed decreasing level of total hemoglobin concentration in all treatment groups specially in group (1).The values of Packed in cell volume (P.C.V) are within normal blood range of rats . Total leucocytes count (W.B.C) decrease in all groups.